2011
DOI: 10.1177/1934578x1100600727
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antibacterial Activity of the Essential Oil of Lantana Camara Var. Moritziana

Abstract: The essential oil obtained from the leaves of Lantana camara var. moritziana (Otto & Dietr.) López-Palacios collected at Rubio, Táchira State, Venezuela, was obtained by hydrodistillation in a Clevenger trap (0.1% yield). The oil was analyzed by gas chromatography-mass spectrometry (GC/MS) on HP GC-MS System, model 5973, identifying 33 compounds (97.1%) of which the major components were germacrene D (31.0%), followed by β-caryophyllene (14.8%), α-phellandrene (6.7%), limonene (5.7%) and 1,8-cineole (5.2%). Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Previous research on the pesticidal plant species used for pest control in this study all have reported bioactivities against insects, parasites, bacteria and fungi (Ganjian et al, 1983 ; Jisaka et al, 1992 ; Lina et al, 1992 ; Pereira et al, 1997 ; Gu et al, 2002 ; Rabe et al, 2002 ; Ogendo et al, 2003 ; Adedire and Akinneye, 2004 ; Boeke et al, 2004 ; Omolo et al, 2004 ; Kawuki et al, 2005 ; Koona and Dorn, 2005 ; Viljoen et al, 2005 ; Koona et al, 2007 ; Ambrósio et al, 2008 ; Asawalam et al, 2008 ; Mujovo et al, 2008 ; Oyewole et al, 2008 ; Bagnarello et al, 2009 ; Chukwujekwu et al, 2009 ; Deng, 2009 ; Gadzirayi et al, 2009 ; Koul and Walia, 2009 ; Madzimure et al, 2011 ; Tesch et al, 2011 ; Chagas-Paula et al, 2012 ; Bartolome et al, 2013 ; Ellse and Wall, 2013 ; Nhamo et al, 2013 ; Utono et al, 2014 ; Green et al, 2017 ; Kamanula et al, 2017 ); however, none of these works have investigated the effects of their application on field crop performance or tritrophic impact. Much is also known about the phytochemistry of the six species evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on the pesticidal plant species used for pest control in this study all have reported bioactivities against insects, parasites, bacteria and fungi (Ganjian et al, 1983 ; Jisaka et al, 1992 ; Lina et al, 1992 ; Pereira et al, 1997 ; Gu et al, 2002 ; Rabe et al, 2002 ; Ogendo et al, 2003 ; Adedire and Akinneye, 2004 ; Boeke et al, 2004 ; Omolo et al, 2004 ; Kawuki et al, 2005 ; Koona and Dorn, 2005 ; Viljoen et al, 2005 ; Koona et al, 2007 ; Ambrósio et al, 2008 ; Asawalam et al, 2008 ; Mujovo et al, 2008 ; Oyewole et al, 2008 ; Bagnarello et al, 2009 ; Chukwujekwu et al, 2009 ; Deng, 2009 ; Gadzirayi et al, 2009 ; Koul and Walia, 2009 ; Madzimure et al, 2011 ; Tesch et al, 2011 ; Chagas-Paula et al, 2012 ; Bartolome et al, 2013 ; Ellse and Wall, 2013 ; Nhamo et al, 2013 ; Utono et al, 2014 ; Green et al, 2017 ; Kamanula et al, 2017 ); however, none of these works have investigated the effects of their application on field crop performance or tritrophic impact. Much is also known about the phytochemistry of the six species evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Like tagitinin A and C, the first two compounds are sesquiterpene lactones which have exhibited antimalarial, antibacterial and cytotoxic activities (Rabe et al, 2002 ; Chukwujekwu et al, 2009 ). The major bioactive components of L. camara are germacrene D, β-caryophyllene, a-phellandrene, limonene, and 1,8-cineole (Tesch et al, 2011 ). Bioactive constituents from B. pilosa include β-caryophyllene and τ-cadinene (Deba et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…As these species clearly grow over a range of habitats and are fast growing, prospects to grow and harvest plant material for the development of botanical pesticide products should be relatively easy to develop. The extent of knowledge on the phytochemistry of the species does vary, with T. vogelii the best studied in terms of knowledge about the chemistry and temporal variations (Belmain et al, 2012;Stevenson et al, 2012); however, phytochemical information is available for all the other species (Adeniyi et al, 2010;Ambrósio et al, 2008;Asawalam et al, 2008;Bartolome et al, 2013;Deba et al, 2008;Ganjian et al, 1983;Green et al, this issue;Gu et al, 2002;Khan et al, 2016;Mkenda et al, 2015;Mujovo et al, 2008;Pereira et al, 1997;Stevenson et al, 2012;Tesch et al, 2011;Viljoen et al, 2005). Producing any of these species as a non-food cash crop would need further evaluation to ensure elite materials were propagated and to fully understand their phytochemistry (Singh, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A survey of the literature indicates that there is a great deal of diversity in the composition of the essential oils of L. camara growing in different localities, and several chemotypes have been described, including a sabinene/cineole/ β ‐caryophyllene chemotype from Nigeria and Iran ; β ‐caryophyllene/ γ ‐muurolene/bicyclogermacrene from Costa Rica ; germacrene D (15.9%), β ‐caryophyllene (12.4%), α ‐humulene (9.3%) from China ; β ‐caryophyllene (34.6%), caryophyllene oxide (10.8%) from Algeria ; β ‐caryophyllene (9.8%), 1,8‐cineole (9.4%), and β ‐pinene (8.2%) from Egypt ; davanone (23.5%), β ‐caryophyllene (11.7%)/sabinene or davanone (15%)/ β ‐caryophyllene (12%) from Madagascar ; β ‐caryophyllene (23.3%), α ‐humulene (11.5%), germacrene D (10.9%) or davanone/ β ‐caryophyllene/bicyclogermacrene from India ; ( E )‐nerolidol (43.4%), δ ‐cadinene (7.6%), from Cuba ; germacrene D (31.0%) and β ‐caryophyllene (14.8%) from Venezuela ; and bicyclogermacrene (19.4%), isocaryophyllene (16.7%), valencene (12.9%), and germacrene D (12.3%) from Brazil . In this report, we have analyzed the essential oil compositions of L. camara collected from different geographical locations: Artemisa in Cuba, Biratnagar in Nepal, and Sana'a in Yemen.…”
Section: Introductionmentioning
confidence: 99%